Indole-3-acetic acid production by rhizobacteria Bacillus spp. to various abiotic stress factors - Veerasamy, Piriya Latha; Ab Aziz, Zakry Fitri; Wong, Sing King; Kasim, Susilawati; Masnindah, Malahubban (2021)
Indole-3-acetic acid (IAA) phytohormone plays an essential role in forming and initiating main, lateral, and adventitious roots in vegetative propagation. Plants are receiving IAA naturally from a diverse group of soil-plant associated rhizobacteria. However, IAA synthesis by rhizobacteria is influenced by abiotic growth condition. Three indigenous Bacillus isolates were subject to in vitro assay for the effects of abiotic factors (temperature, salinity and pH) on growth and IAA production. All isolates grew well between 25 - 40°C, and only B. megaterium UPMLH3 was capable of synthesising IAA (21.18 μg/ml) at 40°C. All three bacterial growth under saline stress were slightly dropped over control (0% NaCl), but still producing IAA up to 1% NaCl condition. B. cereus UPMLH24 revealed high resistance to salinity up to 5% NaCl. Optimum growth of all three Bacillus spp. was at pH 7. B. cereus UPMLH1 and UPMLH24 discovered higher IAA production in slightly alkaline condition (pH 8). Each rhizobacterium shows different physiology trait against each abiotic factor. However, the multiple tolerance ability of PGPR against abiotic factors is an indication that its ability to survive under harsh soil and plant environments while delivering benefits to the plant. Thus, B. cereusUPMLH1, B. megaterium UPMLH3 and B. cereus UPMLH24 might serve as potential biofertiliser, enhancing the growth performance of test plants at various environmental conditions.